Idioms in General English Corpora: on Frequency, Register, and Cross-Variety Variation - Kovaliuk, Yurii (Respectus Philologicus, 2023)
Research into idioms and phraseology has become an established part of the corpus linguistic research agenda and has often revolved around either corpus-based or corpus-driven methodologies. At the same time, a relatively recent approach to socio-variational aspects of language in the form of Cognitive Sociolinguistics has contributed to establishing an ideal platform for the study of variation in the varieties of English. The present paper rests on these two research strands in a survey devoted to variation on the level of idioms in present-day English, namely those denoting competition. While idioms, first and foremost, are theoretically identified with the frameworks of Phraseology, Cognitive Linguistics, and Applied Linguistics, among others, this study will make use of a corpus-based method of idioms introduced by Moon and Gustawsson’s idioms frequency and significance threshold, paired with Moze and Mohamed’s sociolinguistic profiling of idioms. The Idioms will be examined in two national varieties of English, namely those spoken in Great Britain and the USA, which are represented in the British National Corpus and the Corpus of Contemporary American English, respectively. With the assumption that the concept of competition is variety-specific, the main questions to be answered during the analysis are: (1) To what extent can the frequency of use of idioms be regarded an element of variation? and (2) Are there any differences in the prominence of specific variables, such as frequency, register, gender, and age across the two varieties under study? The preliminary findings indicate a significant amount of similarity, but upon closer examination of the data, some important variations are emphasised. Thus, a discussion of the results provides a basis for an inter-variety comparison of the idioms denoting competition and, in so doing, adds to the universality / variation debate.
Keywords: idiom; corpus-based study; the BNC; the COCA; idiom variation